Pengembangan Pemasaran Makanan Berbahan Baku Ketela Untuk Mendukung Wisata Kuliner Di Yogyakarta - Zaenuri, Muchamad; Sulaksono, Tunjung (Universitas Muhammadiyah Yogyakarta, 2016)
Marketing of souvenir products in the form of snacks for tourism services is important. Without good marketing tourists will not know that souvenirs become an alternative for tourists visiting Yogyakarta. Souvenirs in the form of snacks made from cassava into alternative tourists who visit Yogyakarta other than gudeg, bakpia, geplak and soon. Nowdays, the marketing of souvenir products produced by micro, small and medium enterprises (MSMEs) has not been done maximally, just merely dititipkan on certain stalls. The problem has been resolved with the existence of community service programs that have a commitment to fix the marketing of products. By going through the creation of a beautiful cake packaging product design processed products from Mrs. Diah Dharma Astuti and Mrs. Dwi Retnani can attract more buyers. Besides, by giving a sign on the house of both mothers will make it easier for buyers to visit the location. For prospective buyers who from outside the city also menyipakan interesting brochures that contain product specifications and prices. Management assistance activities have also been conducted regu-larly every week. The results of community service activities bring benefits to both MSMEs. By marketing through the website that provides comprehensive information about product specifications through www.jualcakejogja.com page for Dyah Dharma Astuti’s and www.jualkuekeringjogja.com page for Dwi Retnani’s can increase market share and simultaneously increase sales turnover. Marketing of souvenir products in the form of snacks for tourism services is important. Without good marketing tourists will not know that souvenirs become an alternative for tourists visiting Yogyakarta. Souvenirs in the form of snacks made from cassava into alternative tourists who visit Yogyakarta other than gudeg, bakpia, geplak and so on. Nowdays, the marketing of souvenir products produced by micro, small and medium enterprises (MSMEs) has not been done maximally, just merely dititipkan on certain stalls. The problem has been resolved with the existence of community service programs that have a commitment to fix the marketing of products. By going through the creation of a beautiful cake packaging product design processed products from Mrs. Diah Dharma Astuti and Mrs. Dwi Retnani can attract more buyers. Besides, by giving a sign on the house of both mothers will make it easier for buyers to visit the location. For prospective buyers who from outside the city also menyipakan interesting brochures that contain product specifications and prices. Management assistance activities have also been conducted regu- larly every week. The results of community service activities bring benefits to both MSMEs. By marketing through the website that provides comprehensive information about product specifications through www.jualcakejogja.com page for Dyah Dharma Astuti’s and www.jualkuekeringjogja.com page for Dwi Retnani’s can increase market share and simultaneously increase sales turnover. Keywords: marketing, culinary tour, Yogyakarta.